2003
DOI: 10.1021/bp025585a
|View full text |Cite
|
Sign up to set email alerts
|

pH, pCO2, and Temperature Effect on R‐Adenovirus Production

Abstract: The effects of pH, carbon dioxide vapor pressure, pCO(2), and temperature on E1 and E3 deleted recombinant adenovirus vector (rAV) production with HEK293S cells have been studied in the ranges of pH = 6.7-7.7, pCO(2) = 0.05-0.20 atm, and T = 32-39 degrees C, respectively. The experiments were performed in four 500-mL bioreactors in parallel, which make possible the reduction of inter-run variability. Cell concentration and viability, relative oxygen uptake rate (OUR), fluorescence, and viral titer were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 20 publications
8
39
0
Order By: Relevance
“…Higher titers were obtained at 35 and 32°C, with maximum titers being reached at 40 and 74 hpi, respectively. The highest titers were produced at 35°C, which were 3.4-fold higher than at 37°C (Jardon and Garnier 2003). This finding was confirmed by Cortin et al (2004) who showed a 2.4-fold increase in viral titer when 293S cells were cultured at 35°C compared to 37°C.…”
Section: Optimization Of Physicochemical Conditionssupporting
confidence: 58%
See 2 more Smart Citations
“…Higher titers were obtained at 35 and 32°C, with maximum titers being reached at 40 and 74 hpi, respectively. The highest titers were produced at 35°C, which were 3.4-fold higher than at 37°C (Jardon and Garnier 2003). This finding was confirmed by Cortin et al (2004) who showed a 2.4-fold increase in viral titer when 293S cells were cultured at 35°C compared to 37°C.…”
Section: Optimization Of Physicochemical Conditionssupporting
confidence: 58%
“…The virus infection phase is prolonged with increasing pCO 2 , which also decreases the virus yield. The maximum titer at 0.2 atm was 2-fold lower than the maximum titer at 0.05 atm (Jardon and Garnier 2003).…”
Section: Optimization Of Physicochemical Conditionsmentioning
confidence: 66%
See 1 more Smart Citation
“…Shifts of 0.15 units from the optimal growth and production pHs resulted in reductions in specific growth and production rates of 13 and 16%, respectively. Larger changes in pH during culture of hybridoma and other cell lines has resulted in more severe reductions in growth and protein production (Hayter et al, 1992;Jardon and Garnier, 2003), impacted protein glycosylation (Borys et al, 1993; Muthing et al, 2003), and endogenous virus-like particle production (Brorson et al, 2002). As demonstrated in the pH sensitivity plot (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…This leads to an inconsistency between the efficacy obtained from cell culture experiments in vitro and in clinical trials. Therefore, their efficacy of viral oncolysis need to be improved (42)(43)(44)(45). The present study examined whether the enhanced in vitro tumor cytotoxicity, mediated by TSA and H101 in combination, was also exhibited during EC1 cell tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 98%